Effect of pressure on photocatalytic water splitting performance of Z-scheme RP/CH3NH3PbI3 perovskite heterostructure. (8th February 2022) - Li, Peiying; Lin, Yanming; Ma, Mintong; Wang, Qi; Zhang, Minjie; Li, Jiayi; Maheskumar, V.; Wang, Zhengkun; Jiang, Zhenyi; Zhang, Ruiqin
Abstract: Energy is an extremely important strategic material basis for socio-economic development. Here, we have investigated the structural, electronic, optical, charge transfer and photocatalytic mechanism of red phosphorus RP/CH3 NH3 PbI3 heterostructure under hydrostatic pressure by density functional theory (DFT) calculations. Ab initio molecular dynamics (AIMD) prove RP/CH3 NH3 PbI3 is thermodynamically stable. Interestingly, direct band gap of RP/CH3 NH3 PbI3 decreases linearly with increase of pressure. The band gap is 1.43 eV at 1.5 GPa, which can enhance the absorption of visible light and generate redshift in absorption edge. Interface charge redistribution makes valence/conduction band edge positions of RP monolayer and CH3 NH3 PbI3 (010) surface vary with Fermi level, forming an internal electric field have ability to separate electron-hole pairs. Typical Z-scheme heterostructure is formed and supposed to have resulted strong redox ability. The theoretical results hope to provide a possibility for the future experimental preparation of CH3 NH3 PbI3 -based photocatalysts. Graphical abstract: Image 1 Highlights: The band gap of RP/CH3 NH3 PbI3 heterostructure decreases linearly under hydrostatic pressure. Internal electric field of RP/CH3 NH3 PbI3 interface facilitates the separation of electron-hole pairs. Z-scheme RP/CH3 NH3 PbI3 heterostructure has strong redox capacity. The RP/CH3 NH3 PbI3 heterostructure at 1.5 GPa is expected to be a promising photocatalyst.